Association of the rs1990760, rs3747517, and rs10930046 polymorphisms in the IFIH1 gene with susceptibility to autoimmune diseases: a meta-analysis - Xiao, Zilin; Luo, Shuoming; Zhou, Yuemin; Pang, Haipeng; Yin, Wenfeng; Qin, Jiabi; Xie, Zhiguo; Zhou, Zhiguang (Frontiers in Immunology, 2023)
Objective Interferon induced with helicase C domain 1 (IFIH1) single-nucleotide polymorphisms (SNP) rs1990760, rs3747517, and rs10930046 have been shown to be closely related to the risk of autoimmune diseases. The aim of this study was firstly to examine the association of the rs1990760 with type 1 diabetes (T1D) in a Chinese population. Secondly, to assess the association of SNP rs1990760, rs3747517, and rs10930046 with autoimmune diseases susceptibility. Methods A total of 1,273 T1D patients and 1,010 healthy control subjects in a Chinese population were enrolled in this case-control study. Subsequently, we performed a meta-analysis on the association of the SNP rs1990760, rs3747517, and rs10930046 in the IFIH1 gene with susceptibility to autoimmune diseases. The random and fixed genetic effects models were used to evaluate the association and the effect sizes, including odds ratios (OR) and 95% confidence intervals (CI). Stratification analyses based on ethnicity and the type of autoimmune diseases were performed. Results IFIH1 SNP rs1990760 was not associated with a significant risk of T1D in the Chinese population in the case-control study. A total of 35 studies including 70,966 patients and 124,509 controls were identified and included in the meta-analysis. The results displayed significant associations between IFIH1 rs1990760 A allele and rs3747517 C allele and autoimmune diseases risk (OR=1.09, 95% CI: 1.01~1.17; OR=1.24, 95% CI: 1.15~1.25, respectively). Stratified analysis indicated a significant association rs1990760 and rs3747517 with autoimmune diseases risk in the Caucasian population (OR=1.11, 95% CI: 1.02~1.20, OR=1.29, 95% CI: 1.18~1.41, respectively). Conclusions This study revealed no association between IFIH1 SNP rs1990760 and T1D in Chinese. Furthermore, the meta-analysis indicated that rs1990760 and rs3747517 polymorphisms, confer susceptibility to autoimmune diseases, especially in the Caucasian population.